The Impact of Hydrilla Compost on Puspa (Schima wallichii (D.C.) Korth.) Seedling Growth - Delfy Lensari; Yuli Rosianty; Herly Wandi; Sasua Hustati Syachroni (Journal of Global Sustainable Agriculture, 2022)
The Puspa tree (Schima wallichii (D.C.) Korth.) is often used in reforestation and forest restoration activities. Puspa seed propagation techniques can be applied by generative or vegetative plant propagation. The lack of nutrients causes the availability of Puspa seeds very limited. Organic nutrients are used to obtain quality fertile plants and to accelerate growth. In this study, organic nutrients from Hydrilla plants. This study aimed to determine the best application of Hydrilla compost on the growth of Puspa seedlings. The research method used is quantitative. This study used a randomized block design (RBD) with levels of 3 treatments and nine groups, so there were 27, 3 samples were taken for each group, so there were 81 tillers. The treatments in this study were H0 (2000 grams of topsoil), H1 (2000 grams of topsoil and 200 grams of hydrilla compost), and H2 (2000 grams of topsoil and 400 grams of hydrilla compost). The method of work in this research was making hydrilla compost, preparing puspa seeds, planting puspa seeds, and caring for puspa seeds. The observed variables were growth rate (%), number of leaves (strands), plant height (cm), stem diameter (mm), and growing root length (cm). The results showed that the H2 treatment gave the best results for plant heights that were very significantly different, with an average of 8.45 cm, the number of leaves was very significantly different, with an average of 11 strands and root lengths of 4.13 mm.